Analisis Aspek Teknis dan Operasional: (Studi Kasus: Indomaret) - Puspita, Dea; Nayatama S, Muhammad Adhwa; Kusnedi Saragih, Arif (PT. Alahyan Publisher Sukabumi, 2024)
This research explores the technical and operational aspects of Indomaret, one of the leading minimarket chains in Indonesia, which is successful in managing its supply chain and improving service quality. The main focus of this research is on product and service design, as well as quality control implemented by Indomaret. The methodology used is Library Research, which analyzes Indomaret's practices based on relevant literature. The research results show that supply chain planning, store location, and human resource management are key factors in operational success. Indomaret implements a customer feedback system to continuously adapt and make improvements, including employee retraining and improving store facilities. In addition, the use of information technology in inventory management has increased data accuracy and operational efficiency. The conclusions of this research emphasize that a combination of efficiency, service innovation, and focus on quality is the key to success in the competitive retail market. Suggestions for Indomaret include adopting the latest technology and improving user experience.